Item Features Interact With Item Category in Their Influence on Preferences - Oren, Shiran; Sela, Tal; Levy, Dino J.; Schonberg, Tom (Frontiers in Psychology, 2020)
Low-level visual features are known to play a role in value-based decision-making. However, most previous studies focused on this role of only a single low-level feature or only for one type of item. These studies also used only one method of measurement and provided a theory accounting for those specific findings. We aimed to utilize a different more robust approach. We tested the contribution of low-level visual features to value-based decision making of three item types: fractal-art images, faces, and snack food items, and used two techniques to estimate values: subjective ratings and actual choices. We found that low-level visual features contribute to value-based decision-making even after controlling for higher level features relevant for each item category (for faces features like eye-distance and for food snacks features like price and calories). Importantly, we show that overall, while low-level visual features consistently contribute to value-based decision-making as was previously shown, different features contribute distinctively to preferences of specific item types, as evident when we estimated values using both techniques. We claim that theories relying on the role of single features for individual item types do not capture the complexity of the contribution of low-level visual features to value-based decision-making. Our conclusions call for future studies using multiple item types and various measurement methods for estimating value in order to modify current theories and construct a unifying framework regarding the relationship between low-level visual features and choice.